CUIDADOS DE ENFERMAGEM À PACIENTES EM ISOLAMENTO DE CONTATO POR Acinetobacter EM UTI - Nicoletti, Andrelise M.; Simão, Juciara; Silva, Luiz A. A. d.; Stumm, Eniva M. F.; Scheuer, Cléber; Bohn, Jonathan A. (Salão do Conhecimento, 2013)
Resumo